The lucky ones - Jackson, Linda Williams (Candlewick Press, 2022)
In 1967, eleven-year-old Ellis Earl Brown has big dreams for his future. He's going to become a teacher or a lawyer, live in a big brick house in town, and always have enough food to feed his family. He makes sure to work hard in school, but when he learns he might need to quit school to help support the family, his future is put in jeopardy. With the support of his teacher, Mr. Foster, Ellis Earl tries to find a way to show his mother the value of a good education.